Bioluminescent RIPoptosome Assay for FADD/RIPK1 Interaction Based on Split Luciferase Assay in a Human Neuroblastoma Cell Line SH-SY5Y - Parisa Ghanavatian; Hossein Salehi-Sedeh; Farangis Ataei; Saman Hosseinkhani (Biosensors, 2023)
Different programed cell death (PCD) modalities involve protein–protein interactions in large complexes. Tumor necrosis factor α (TNFα) stimulated assembly of receptor-interacting protein kinase 1 (RIPK1)/Fas-associated death domain (FADD) interaction forms Ripoptosome complex that may cause either apoptosis or necroptosis. The present study addresses the interaction of RIPK1 and FADD in TNFα signaling by fusion of C-terminal (CLuc) and N-terminal (NLuc) luciferase fragments to RIPK1-CLuc (R1C) or FADD-NLuc (FN) in a caspase 8 negative neuroblastic SH-SY5Y cell line, respectively. In addition, based on our findings, an RIPK1 mutant (R1C K612R) had less interaction with FN, resulting in increasing cell viability. Moreover, presence of a caspase inhibitor (zVAD.fmk) increases luciferase activity compared to Smac mimetic BV6 (B), TNFα -induced (T) and non-induced cell. Furthermore, etoposide decreased luciferase activity, but dexamethasone was not effective in SH-SY5Y. This reporter assay might be used to evaluate basic aspects of this interaction as well as for screening of necroptosis and apoptosis targeting drugs with potential therapeutic application.